2018
DOI: 10.1016/j.jas.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between cutting actions on bone using 3D geometric morphometrics and Bayesian analyses with implications to human evolution

Abstract: Studies of bone surface modifications (BSMs) such as cut marks are crucial to our understanding of human and earlier hominin subsistence behavior. Over the last several decades, however, BSM identification has remained contentious, particularly in terms of identifying the earliest instances of hominin butchery; there has been a lack of consensus over how to identify or differentiate marks made by human and non-human actors and varying effectors. Most investigations have relied on morphology to identify butcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 81 publications
1
46
1
Order By: Relevance
“…Research on bone surface modifications has been enhanced by the use of quantitative 3D methods [ 33 38 ]. These approaches and others that utilize confocal microscopy and 3D surface texture analysis [ 39 ] have appreciably reduced intra-observer error.…”
Section: Introductionmentioning
confidence: 99%
“…Research on bone surface modifications has been enhanced by the use of quantitative 3D methods [ 33 38 ]. These approaches and others that utilize confocal microscopy and 3D surface texture analysis [ 39 ] have appreciably reduced intra-observer error.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they are using Bayesian modeling in free computer platforms to refine absolute chronologies to an unprecedented degree—a second radiocarbon revolution (e.g., Fitzpatrick and Jew ; Hamilton and Krus ; Lulewicz ; Miller ; Otárola‐Castillo et al. ).…”
Section: Methodological and Epistemological Advancesmentioning
confidence: 99%
“…In fact, some methodological studies reported the best practices [6,13,14], and UCR-DP has already been widely applied in fields closely related to the anthropological research, such as archaeology and cultural heritage-for the surveying, interpretation and virtual reconstruction of excavation sites, caves, buildings, monuments [9,12,15,16], documenting statues, bas-relief and mosaics [17,18], building 3D repositories of museum collections [19]-and palaeontology, particularly for site interpretation and track site documentation [13,20,21], other than for digitising bones from mounted skeletons [22]. A number of applications have also been developed in anthropology for documenting rock art [23][24][25][26][27], artefacts [28,29], cut and percussion marks due to human activity [30][31][32][33][34], and hominin footprints [35].…”
Section: Introductionmentioning
confidence: 99%